A case of complete double aortic arch visualized by transthoracic echocardiography. Issue 8 (6th July 2017) - Saito, Naka; Kato, Shingo; Saito, Noritaka; Nakachi, Tatsuya; Fukui, Kazuki; Iwasawa, Tae; Kosuge, Masami; Kimura, Kazuo
Abstract : A case of double aortic arch that was well visualized using transthoracic echocardiography is reported. A 38‐year‐old man underwent transthoracic echocardiography for the evaluation of dyspnea. A suprasternal view of transthoracic echocardiography showed the ascending aorta bifurcate to left and right aortic arches, with blood flow from the ascending aorta to bilateral aortic arches. The diagnosis of right side–dominant double aortic arch was made, and the patient's symptom was conceivably related to compression of the trachea due to a vascular ring. This report indicates the potential usefulness of transthoracic echocardiography for noninvasive detection of double aortic arch in adults.